ADAM9 Genetic Variants and Their Role in Modulating Enzyme Activity in Diabetes and Metabolic Traits - Hana Drobiova; Fahd Al-Mulla; Rabeah Al-Temaimi (Journal of Diabetes Research)
A disintegrin and metalloproteinase Domain 9 (ADAM9) is a zinc-dependent proteinase involved in various biological processes. However, its role in the pathophysiology of metabolic syndrome remains unclear, and studies exploring the association between ADAM9 polymorphisms and metabolic traits are limited. In this study, we investigated the potential link between ADAM9 variants and metabolic syndrome traits in a cohort of adult participants from Kuwait. Using a genome-wide association study (GWAS), followed by a replication study, we identified two ADAM9 variants—ADAM9-E76K (rs61753672) and ADAM9-P750L (rs144750648)—that were associated with various metabolic traits. The replication phase confirmed the association of ADAM9-P750L with HbA1c levels and revealed new associations with systolic blood pressure, waist-to-hip ratio, fasting blood glucose, triglycerides, and cholesterol. Functional analysis showed that both variants exhibited reduced proteolytic activity, potentially contributing to the pathogenesis of Type 2 diabetes. These findings suggest that ADAM9 variants may play a significant role in metabolic health and diabetes risk.